The intensity of judicial review in political disputes: measuring the merits and the risks - Kadouf, Hunud Abia; Sambo, Abdulfatai. O (penseejournal.com, 2014)
In institutional democratic regime, courts have a difficult task in resolving questions which are political in nature though with legal and constitutional elements. yet, the courts have a role to serve as checks and balance, defender of the rights of common man and as an institution where disputes are resolved with finality. This paper analyses the merits and risk involved in intensifying the exercise of judicial review power in political disputes. In doing this, the paper discusses the theoretical framework; relating to the exercise of judicial review power. From there, it analyses the merits and the risks involved. It makes use of content analysis of legal issues, constitutions and interviews with some stakeholders to enrich the legal analysis. The aim is to ensure sustainable peace in the democratic dispensation in developing nations. The paper finds that although intensity of judicial review in developing nations has to its merits,it also carries with it a risky undertaking